2021
DOI: 10.1096/fasebj.2021.35.s1.02918
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the hyoid musculature in the snow leopard ( Panthera uncia )

Abstract: The snow leopard (Panthera uncia) is currently considered vulnerable by the IUCN, with approximately 5,000 individuals left in the wild with a 20% decline in their population in the last two decades. The hyoid apparatus of this felid has been documented, but the musculature of this region has not. The hyoid region of snow leopards is of interest because they have an incompletely ossified hyoid apparatus and they produce distinctive vocalizations among the Felidae. Similar to other pantherines, the snow leopard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Weissengruber et al (2002) have suggested that this elastic ligament may allow for a lower laryngeal position, which is correlated with lower frequency vocalizations in other species (Tecumseh Fitch & Reby, 2001). Despite having a similarly unossified epihyoid, the fifth member of the monophyletic genus, Panthera uncia , is unable to either purr or roar; this has been attributed to differences in other soft‐tissue anatomy (Assar et al, 2021; Hast, 1989; Peters & Hast, 1994). All cats within the subfamily Felinae, are able to purr and have fully ossified epihyoid bones (Peters & Hast, 1994; Peters, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Weissengruber et al (2002) have suggested that this elastic ligament may allow for a lower laryngeal position, which is correlated with lower frequency vocalizations in other species (Tecumseh Fitch & Reby, 2001). Despite having a similarly unossified epihyoid, the fifth member of the monophyletic genus, Panthera uncia , is unable to either purr or roar; this has been attributed to differences in other soft‐tissue anatomy (Assar et al, 2021; Hast, 1989; Peters & Hast, 1994). All cats within the subfamily Felinae, are able to purr and have fully ossified epihyoid bones (Peters & Hast, 1994; Peters, 2002).…”
Section: Introductionmentioning
confidence: 99%